"A father doesn’t just have to pay the bills and be all manly" : constructions of fathering among adolescents in a low-income, high violence community in Cape Town - Helman, Rebecca (Department of Psychology, 2015)
In light of research which suggests that father involvement is associated with positive outcomes for children, including emotional, social and financial benefits, the high rate of father absence in South Africa has been interpreted as a ‘crisis’ of fatherhood (Ratele, Shefer, & Clowes, 2012). However, there is a lack of research that explores fathering and fatherhood from the perspective of South African children. This study aimed to investigate the ways in which a group of nine female and five male adolescents in an urban, low-income community of Cape Town discursively construct the roles and responsibilities of fathers in their community. Using Photovoice methodology, participants produced photographs of ‘fathering in my community’ and then participated in a photo-elicitation interview. The interview transcripts were subjected to a discourse analysis to identify discursive constructions of fatherhood. Consistent with previous research which has been conducted with fathers, participants drew on hegemonic discourses which positioned fathers as financial providers and protectors, and mothers as ‘natural’ care-givers and nurturers. Fathers were predominantly represented as failing to fulfil their roles and responsibilities. However, there were also instances in which participants resisted these dominant discourses through drawing on a discourse of ‘involved’ fathering which positioned fathers as nurturers and carers. Participants also discursively constructed a form of non-biological ‘social father’ who could fulfil some fathering roles. In light of these findings it appears that there is a need to challenge rigid and inflexible hegemonic constructions of fathering (and masculinity more generally), and to elaborate contesting versions of fatherhood, in order to make alternative, more fluid subject positions available to men as fathers.